PENDIDIKAN KARAKTER PADA ANAK USIA DINI - Nuraeni Nuraeni (Universitas Pendidikan Mandalika, 2016)
Embedding character values from an early age is a shared responsibility between parents, educators, caregivers, society and the government. For this reason, togetherness, harmony and partnership in instilling character values from an early age must be cultivated and optimized together. Collaboration with parents can be done through socialization so that the character values that have been used in PAUD institutions can also be carried out at home. For the community and the government, it is hoped that support can also be obtained by creating an atmosphere that is conducive to the formation of character for early childhood. Character values that are considered very important to be introduced and applied to behavior in early childhood include: love for God Almighty, honesty, discipline, tolerance and love of peace, self-confidence, independence, help, cooperation, mutual cooperation, respect and courtesy. , responsibility, hard work, leadership and justice, creative, humble, caring for the environment, love for the nation and homeland.